2012
DOI: 10.1158/1541-7786.mcr-11-0281
|View full text |Cite
|
Sign up to set email alerts
|

STEAP Proteins: From Structure to Applications in Cancer Therapy

Abstract: The human 6-transmembrane epithelial antigen of prostate (STEAP) family comprises STEAP1, STEAP2, STEAP3, and STEAP4. All of these proteins are unique to mammals and share an innate activity as metalloreductases, indicating their importance in metal metabolism. Overall, they participate in a wide range of biologic processes, such as molecular trafficking in the endocytic and exocytic pathways and control of cell proliferation and apoptosis. STEAP1 and STEAP2 are overexpressed in several types of human cancers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
228
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(231 citation statements)
references
References 82 publications
3
228
0
Order By: Relevance
“…This N-terminal domain works in conjunction with the C-terminal transmembrane domain to confer cell surface ferric and cupric reductase activity to these larger Steap2-4 family members (2,3). Steap1 and Steap2 are highly overexpressed in a number of different human cancers (prostate, bladder, colon, pancreas, ovary, testis, breast, cervix, and Ewing sarcoma) (4 -6); however, their roles in both normal and cancer cells are not well understood (7). In contrast, Steap3 is the only family member for which a clear physiological role has been demonstrated.…”
mentioning
confidence: 99%
“…This N-terminal domain works in conjunction with the C-terminal transmembrane domain to confer cell surface ferric and cupric reductase activity to these larger Steap2-4 family members (2,3). Steap1 and Steap2 are highly overexpressed in a number of different human cancers (prostate, bladder, colon, pancreas, ovary, testis, breast, cervix, and Ewing sarcoma) (4 -6); however, their roles in both normal and cancer cells are not well understood (7). In contrast, Steap3 is the only family member for which a clear physiological role has been demonstrated.…”
mentioning
confidence: 99%
“…In several types of human cancers such as prostate, cervix, ovary, testis, breast, colon, pancreas, iEwing sarcoma and bladder, the expression of STEAP1 and STEAP2 is significantly high. The expression of this family is different in normal and cancerous tissue making them possible candidate for the therapeutic strategies [18]. Previous studies have shown that the expression of STEAP2 is 10 times higher in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In PCa, MMPs -2, -7, -9, -13 and -14 have been shown to be involved and their over-expression promotes PCa growth and metastasis [2]. In early endosomes and the TGN Trans Golgi network STEAP2 can also be found and it acts as a receptor for both exogenous and endogenous ligands or as regulator of protein delivery and sorting mechanisms [2,18].…”
mentioning
confidence: 99%
“…One metal-reductase involved could be Dcytb, a cytochrome b family homologue, which has been shown to be expressed in cultured astrocytes [60,66]. Astrocytes also contain the mRNAs of proteins of the 6-transmembrane epithelial antigen of prostate (Steap) family, suggesting that astrocytes may also contain the respective proteins which have extracellular cuprireductase activity [67][68][69].…”
Section: Uptake Of Low Molecular Weight Coppermentioning
confidence: 99%